2017
DOI: 10.4172/2573-0347.1000144
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Concept of Competence in Nursing Education

Abstract: Aim: The purpose of this paper is to present an analysis of the concept of competence of nurses and examine how competence is currently measured.Background: Nurse Education curricula have adopted a competency based model without clear and unequivocal understanding of the meaning of competence. Competence is reported to be developed incrementally and individually situated in a binary definition, these two positions have lead to confusion within nursing practice and nurse education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…As a result, previous works (Hayton & McEvoy 2006;Miller, Wesley & Williams 2012) reveal that a significant complication in the literature on competence is that there are many definitions of the term, and that the terms expertise, skills, competency and acumen, although interrelated, are occasionally used interchangeably. There is a lot of confusion and debate regarding the term 'competence' and it is almost impractical to identify a comprehensive theory or to coin a definition that can accommodate and reconcile all the diverse ways that the word is used (Scanlon 2017). Even though Boon and Van der Klink (2003) regarded competence as a 'fuzzy concept', they admit that it is a worthwhile term, which bridges the gap between job requirements and education.…”
Section: Managerial Competencies and Performancementioning
confidence: 99%
“…As a result, previous works (Hayton & McEvoy 2006;Miller, Wesley & Williams 2012) reveal that a significant complication in the literature on competence is that there are many definitions of the term, and that the terms expertise, skills, competency and acumen, although interrelated, are occasionally used interchangeably. There is a lot of confusion and debate regarding the term 'competence' and it is almost impractical to identify a comprehensive theory or to coin a definition that can accommodate and reconcile all the diverse ways that the word is used (Scanlon 2017). Even though Boon and Van der Klink (2003) regarded competence as a 'fuzzy concept', they admit that it is a worthwhile term, which bridges the gap between job requirements and education.…”
Section: Managerial Competencies and Performancementioning
confidence: 99%
“…Lack of competence is also regarded as one of the main causes of dissatisfaction among nurses. In the organizational aspect, the availability of competent staff not only reduces the costs but also is associated with the use of available resources and facilities (17).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the results of this study suggest that 1 year may not be sufficient to appreciate an increase in the level of competence of new graduates. According to Scanlon (2017), the threshold for a nurse to achieve the level of being competent in practice varies. Although the first 6 months after graduation is a crucial period for new graduate nurses to reinforce clinical competence, Cheng et al (2014) suggested that new graduates still need to have at least 12 months to feel comfortable to work in a new environment.…”
Section: Resultsmentioning
confidence: 99%
“…Benner (1984) argued that a newly registered practitioner becomes competent only with a degree of exposure to that role for 2-3 years after the point of registration. However, it is acceptable to expect that a person is competent at the level of registration (Scanlon, 2017). Besides, the professional licensure examination system ensures that the person bearing the license has met the minimum or entry-level competencies to perform acts allowed by the license (Oducado, Cendaña, & Belo-Delariarte, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation